Carbon-based Membranes for Separation Processes - Ismail, Ahmad Fauzi; Rana, Dipak; Matsuura, Takeshi; Foley, Henry C.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
This book provides a significant overview of carbon-related membranes. It will cover the development of carbon-related membranes and membrane modules from its onset to the latest research on carbon mixed matrix membranes. After reviewing progress in the study of membrane processes, the book discusses future research directions and prospective development in that field. A guideline is provided for readers who would like to establish their own laboratories for carbon membrane research. For this purpose, detailed information on preparation, characterization, and testing of various types of carbon membrane is provided. Design and construction of carbon membrane modules are also described in detail.
Introduction -- Transport mechanism through carbon membranes -- Configuration of carbon membranes -- Preparation of carbon membranes -- Membrane testing -- Membrane characterization -- Membrane module constructions -- Other carbon based membranes -- Applications of carbon-based membranes for separation processes -- Economics of carbon-based membranes -- Future research direction of carbon-based membranes.
Keywords: Chemical engineering; Organic chemistry; Polymers .; Analytical chemistry; Environmental chemistry; Industrial Chemistry/Chemical Engineering; Organic Chemistry; Polymer Sciences; Analytical Chemistry; Environmental Chemistry